High-temperature-resistant diaphragm for lithium battery as well as preparation method and application of high-temperature-resistant diaphragm
By applying a high heat-resistant coating slurry to the lithium-ion battery separator, the problem of poor safety of the existing separator at high temperatures is solved, the high temperature resistance and ionic conductivity of the separator are improved, and the safety performance and performance stability of the battery are enhanced.
Patent Information
- Application Number
- CN202510396716.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing lithium-ion battery separators are prone to safety problems at high temperatures, and it is difficult to effectively improve their high temperature resistance and ionic conductivity.
By mixing water, dispersant and inorganic ceramic materials evenly, stirring and grinding to obtain a mixed liquid, and mixing it with modified acrylic polymer binder, polyacrylamide polymer binder and wetting agent to form a high heat-resistant coating slurry, coated on the surface of the polyolefin-based film, and a high temperature-resistant lithium battery separator is prepared.
It significantly improves the high temperature resistance and ionic conductivity of the lithium battery separator, and enhances the safety performance and performance stability of the battery.
Smart Images

Figure CN119921053A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a high temperature resistant diaphragm for lithium batteries and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of small size, high voltage, high energy density, low self-discharge rate, no memory effect, high specific energy, wide operating temperature range, fast high-rate charge and discharge, and low pollution to the environment. It is a promising energy storage device that integrates renewable resources and high-power applications. The diaphragm is a plastic film with rich pore structure and uniform pore size distribution, which can ensure the free passage of lithium ions to form a circuit and prevent the two electrodes from contacting each other to play the role of electronic insulation. Although the diaphragm does not directly participate in the redox reaction inside the battery, the physicochemical properties of the diaphragm, such as thickness, pore size, porosity, and closed-cell temperature, are closely related to the key properties of the battery, such as internal resistance, capacity, cycle performance, and safety performance, and directly affect the electrochemical performance of the battery.
[0003] For power lithium-ion batteries, the influence of the diaphragm on the rate performance and safety performance of the battery is more significant. With the continuous advancement of science and technology, it is crucial to study and prepare diaphragms with excellent comprehensive performance for the future development of lithium-ion batteries. At present, polyethylene (PE) and polypropylene (PP) are commonly used as diaphragms. Polyolefins have good chemical and electrochemical stability as diaphragm materials and have certain mechanical strength, but their disadvantages are also very obvious. They are difficult to be infiltrated by electrolytes, which is not conducive to the performance of batteries. In addition, PE and PP have relatively low melting points and shrink significantly at 130-160°C. When the battery is abnormally heated, it is easy to cause safety problems. Summary of the invention
[0004] The present application provides a high temperature resistant diaphragm for lithium batteries and a preparation method and application thereof to solve the problems in the above-mentioned background technology.
[0005] In a first aspect, the present application provides a method for preparing a high temperature resistant diaphragm for a lithium battery, comprising: Mix water, a dispersant and an inorganic ceramic material uniformly, stir and grind to obtain a mixed solution, wherein the mass ratio of the water, the dispersant and the inorganic ceramic material is (65-75): (0.5-0.8): (35-25); The modified acrylic polymer binder, the polyacrylamide polymer binder, the wetting agent and the mixed solution are uniformly mixed to obtain a high heat-resistant coating slurry, wherein the mass ratio of the modified acrylic polymer binder, the polyacrylamide polymer binder, the wetting agent and the inorganic ceramic material is (1.5-2.5): (1.5-2.5): (0.03-0.06): 100; The high heat-resistant coating slurry is applied to two opposite sides or any one side of a polyolefin base film to form a coating on the corresponding side of the polyolefin base film, and after drying, a high-temperature resistant separator for a lithium battery is obtained.
[0006] Furthermore, the stirring time of the water, the dispersant and the inorganic ceramic material is 15-60 minutes, and the grinding time is 40-60 minutes.
[0007] Furthermore, the inorganic ceramic material is any one of alumina, boehmite and silica.
[0008] Furthermore, the dispersant is polycarboxylate ammonium salt.
[0009] Furthermore, the modified acrylic acid polymer binder, the polyacrylamide polymer binder, the wetting agent and the mixed solution are stirred for 15-30 minutes.
[0010] Furthermore, the molecular weight of the polymer in the modified acrylic acid polymer binder is 80,000 to 200,000, and the molecular weight of the polymer in the polyacrylamide polymer binder is 200,000 to 600,000.
[0011] Furthermore, the wetting agent is a polyether siloxane copolymer.
[0012] Furthermore, the polyolefin-based film is a polyethylene film or a polypropylene film, the coating method is roller coating, the thickness of each coating is 2-4 μm, the drying temperature is 50-80° C., and the drying time is 30-60 s.
[0013] In a second aspect, the present application provides a high temperature resistant diaphragm for a lithium battery, which is obtained based on the preparation method of the high temperature resistant diaphragm for a lithium battery as described above.
[0014] In a third aspect, the present application provides the application of the high temperature resistant separator for lithium batteries as described above in the field of lithium batteries.
[0015] The above technical solution of the present application has the following advantages: The first aspect of the present application provides a method for preparing a high-temperature resistant diaphragm for a lithium battery. A mixed solution is obtained by using water, a dispersant and an inorganic ceramic material, a high-heat-resistant coating slurry is obtained by using a modified acrylic polymer binder, a polyacrylamide polymer binder, a wetting agent and the mixed solution, and the high-heat-resistant coating slurry is coated on the surface of a polyolefin base film to prepare a high-temperature resistant diaphragm for a lithium battery. The application of polyacrylic acid in the inorganic coating can greatly improve the high-temperature resistance of the diaphragm, thereby improving the heat resistance of the polyolefin diaphragm and the safety of the lithium battery. In combination with the inorganic ceramic material, the ionic conductivity of the diaphragm can be further improved while improving the wettability.
[0016] It can be understood that the beneficial effects of the second and third aspects mentioned above can be found in the relevant description of the first aspect mentioned above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 SEM images of Comparative Example 2(a), Comparative Example 1(b), Example 1(c), and Example 2(d) provided in this application; Figure 2 The contact angle diagrams of Comparative Example 2(a), Example 1(b), Example 2(c) and Comparative Example 1(c) provided in the present application; Figure 3 The thermal shrinkage diagrams at different temperatures of Comparative Example 2, Comparative Example 1, Example 1 and Example 2 provided in the present application. DETAILED DESCRIPTION
[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0020] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0021] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0022] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0023] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also indicate the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as µg, mg, g, kg, etc.
[0024] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0025] The specific implementation methods of the present application are further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present application but are not intended to limit the scope of the present application.
[0026] The present application provides a method for preparing a high-temperature resistant diaphragm for a lithium battery, comprising: uniformly mixing water, a dispersant and an inorganic ceramic material, stirring and grinding to obtain a mixed liquid, wherein the mass ratio of the water, the dispersant and the inorganic ceramic material is (65-75): (0.5-0.8): (35-25); uniformly mixing a modified acrylic polymer binder, a polyacrylamide polymer binder, a wetting agent and the mixed liquid to obtain a high-heat-resistant coating slurry, wherein the mass ratio of the modified acrylic polymer binder, the polyacrylamide polymer binder, the wetting agent and the inorganic ceramic material is (1.5-2.5): (1.5-2.5): (0.03-0.06): 100; applying the high-heat-resistant coating slurry to two opposite sides or any one side of a polyolefin base film to form a coating on the corresponding side of the polyolefin base film, and obtaining a high-temperature resistant diaphragm for a lithium battery after drying.
[0027] Inorganic materials such as alumina and boehmite are very stable in the range of 100-300℃, and their micro / nano materials have been commercialized. When a layer of inorganic coating is covered on the surface of the polyolefin separator, even if the base film melts during the battery charging and discharging process, the inorganic coating can still maintain the integrity of the separator and prevent the occurrence of large-area positive / negative short circuits, providing a feasible solution to solve the safety of high-power batteries. However, conventional binders used in inorganic coatings will fail due to temperature increases, causing the coating to fall off, thereby reducing the high temperature resistance of the coating film.
[0028] In view of the above shortcomings, the present application provides a method for preparing a high temperature resistant diaphragm for lithium batteries. The preparation method introduces a high heat resistant coating slurry on the surface of a polyolefin diaphragm, and polyacrylic acid is applied to the inorganic coating to greatly improve the high temperature resistance of the diaphragm, thereby improving the heat resistance of the polyolefin diaphragm, improving the safety of lithium batteries, and improving the ionic conductivity of the diaphragm. The high temperature resistant diaphragm for lithium batteries obtained by the above preparation method can solve the problem of coating shedding of inorganic coating diaphragms at high temperatures and improve the high temperature resistance of the diaphragm.
[0029] In some embodiments, the stirring time of the water, the dispersant and the inorganic ceramic material is 15-60 min, and the grinding time is 40-60 min.
[0030] In some embodiments, the inorganic ceramic material is any one of alumina, boehmite and silica.
[0031] In some embodiments, the dispersant is a polycarboxylate ammonium salt.
[0032] In some embodiments, the modified acrylic polymer binder, the polyacrylamide polymer binder, the wetting agent and the mixed solution are stirred for 15-30 minutes.
[0033] In some embodiments, the molecular weight of the polymer in the modified acrylic acid polymer binder is 80,000 to 200,000, and the molecular weight of the polymer in the polyacrylamide polymer binder is 200,000 to 600,000.
[0034] In some embodiments, the wetting agent is a polyether siloxane copolymer.
[0035] In some embodiments, the polyolefin-based film is a polyethylene film or a polypropylene film, the coating method is roller coating, the thickness of each coating is 2-4 μm, the drying temperature is 50-80° C., and the drying time is 30-60 s.
[0036] The water, dispersant and inorganic ceramic material are mixed uniformly and ground to obtain a mixed solution, wherein the ratio of water, dispersant and inorganic ceramic material is (65-75): (0.5-0.8): (35-25) by mass fraction; the mixed solution is achieved by stirring, the stirring time is 15-60 minutes, and the grinding time is 40-60 minutes. The inorganic ceramic material is any one of alumina, boehmite and silicon dioxide; the dispersant is polycarboxylic acid ammonium salt.
[0037] The binder 1, binder 2, wetting agent and mixed liquid are mixed evenly, and the mixing is achieved by stirring for 15-30 minutes to obtain a high heat-resistant coating slurry. Among them, the binder 1 is a modified acrylic polymer binder with a polymer molecular weight of 80,000 to 200,000, the binder 2 is a polyacrylamide polymer binder with a polymer molecular weight of 200,000 to 600,000, and the wetting agent is a polyether siloxane copolymer. In terms of mass fraction, the ratio of the modified acrylic polymer binder, the polyacrylamide polymer binder, the wetting agent and the inorganic ceramic material is (1.5-2.5): (1.5-2.5): (0.03-0.06): 100.
[0038] The above preparation method obtains a high heat-resistant coating slurry. The high heat-resistant coating slurry is applied to the two opposite sides or any one side of the polyolefin base film to form a layer on the corresponding surface of the polyolefin base film, and dried to obtain a high-temperature resistant diaphragm for a lithium battery. The polyolefin base film is a polyethylene film or a polypropylene film, and the coating method is roller coating. The thickness of each coating is 2-4μm, the drying temperature is 50-80℃, and the drying time is 30-60s. The application of polyacrylic acid in inorganic coatings can greatly improve the high temperature resistance of the diaphragm. In combination with inorganic ceramic materials, the ionic conductivity of the diaphragm can be further improved while improving the wettability.
[0039] The technical solution of the present application is further explained below in conjunction with specific embodiments. Example
[0040] Dispersant, Al 2 O 3 Dissolve in deionized water, stir for 30 min until completely dissolved to obtain a mixed solution, the rotation speed is 600 rpm; deionized water, dispersant and Al 2 O 3 The mass ratio of is 65:0.5:35; zirconium oxide (spherical) is added to the mixed solution for grinding, the grinding time is 60 minutes, the rotation speed is 1100rpm, and the zirconium oxide is filtered out after the grinding; Add modified acrylic polymer binder, polyacrylamide polymer binder and wetting agent to the filtered mixed solution, stir for 15 minutes until uniformly mixed to obtain high heat-resistant coating slurry, the rotation speed is 300 rpm; modified acrylic polymer binder, polyacrylamide polymer binder, wetting agent and Al 2 O 3 The mass ratio is 2.5:1.5:0.03:100; The obtained high heat-resistant coating slurry was used to coat a single side of the 7 μm base film, with a coating thickness of 3 μm. The film was placed in a 60° C. oven and dried for 60 seconds until dried to obtain a high-temperature resistant separator for lithium batteries, which was then taken out for use. Example
[0041] The inorganic ceramic material used in this embodiment is boehmite, and the rest of the preparation process is consistent with that in Embodiment 1.
[0042] The binder used in this comparative example is the binder used for conventional ceramic coating diaphragms, and the rest of the preparation process is consistent with Example 1.
[0043] PE base film.
[0044] The above four types of diaphragms were subjected to SEM, contact angle, thermal shrinkage and other tests, and the results are as follows: The above four types of diaphragms were subjected to SEM tests, as shown in the attached Figure 1 As shown in the attached Figure 1 In (a), it can be clearly seen that the surface of the PE base film of Comparative Example 2 is distributed with irregular micron and submicron through holes, which provide an effective channel for the transmission of lithium ions. Figure 1 As can be seen from (b), (c) and (d), there is basically no difference in the surface morphology between the embodiment and the comparative example. 2 O 3 and boehmite particles were successfully coated on the surface of the PE base film and evenly distributed. 2 O 3 The particles can significantly improve the wettability and thermal stability of PE-based films.
[0045] Wettability is one of the important properties of lithium battery separators. The contact angles of the four separators were tested. The results are shown in the attached figure. Figure 2 As shown in Table 1, the PE base film of Comparative Example 2 has the worst wettability, with an average contact angle of 118°, indicating that the wettability of the PE base film with the electrolyte is poor, which in turn affects the internal resistance and cycle stability of the battery. 2 O 3The wettability of the composite membrane with boehmite particles has been greatly improved, and the contact angles have been reduced to 17.1°, 13.9° and 21°. Since water and electrolyte have the same polarity, this result also shows that the composite membrane can better absorb electrolyte and effectively promote the transmission of lithium ions in the membrane, thereby reducing the internal resistance of the battery and improving the cycle efficiency and stability of the battery.
[0046] Table 1 Contact angles of different membranes The thermal stability of lithium battery separators is very important. Highly heat-resistant lithium-ion battery separators can effectively improve battery safety. The thermal stability of the above three separators was tested at 120℃, 150℃ and 180℃ for 30 minutes. The results are shown in Table 2 and attached. Figure 2 As shown in Table 2, the composite membrane coating thickness obtained in Example 1, Example 2 and Comparative Example 1 is about 3 μm. As the membrane thickness increases, the membrane permeability value also increases, with an increase of about 30, which meets the experimental standard. Figure 2 It can be clearly seen that the PE diaphragm shrinks slightly at 120°C, melts at 150°C, shrinks significantly, and the shrinkage rate reaches 67%. The diaphragm of Comparative Example 1 can still maintain a certain morphology at 150°C, and the shrinkage rate is only 4%, which is significantly improved compared with the PE base film. This is because the Al in the coating 2 O 3 The composite membranes of Example 1 and Example 2 still maintained their shape and did not break at 180°C because they used a high-temperature resistant polyacrylamide polymer binder. This proves that the safety of the membrane is greatly improved.
[0047] Table 2 Thickness, air permeability and MD and TD distance of different diaphragms at different temperatures In summary, the composite diaphragm using polyacrylamide polymer binder has significantly improved thermal stability compared to PE-based film and composite diaphragm using ordinary binders, thereby improving the safety performance of the diaphragm under special conditions.
[0048] This application uses inorganic particles and polyacrylamide polymer as a binder to prepare a new coating material, and uses a simple and low-cost coating modification method to prepare a lithium-ion battery separator. The separator has good wettability and excellent thermal stability. It has no obvious shrinkage when placed at 180°C for 30 minutes, which effectively improves the safety of the lithium-ion battery separator.
[0049] The present application also provides a high temperature resistant diaphragm for a lithium battery, which is obtained based on the preparation method of the high temperature resistant diaphragm for a lithium battery as described above.
[0050] The present application also provides the use of the high temperature resistant separator for lithium batteries as described above in the field of lithium batteries.
[0051] This application uses polyacrylamide polymer as a binder. 2 O 3 A new coating material is prepared for the main inorganic particles, and a lithium-ion battery separator is prepared by a coating modification method. The application is an aqueous slurry, which is simple to prepare and environmentally friendly. The separator has good wettability and excellent thermal stability, which effectively improves the safety of the lithium-ion battery separator.
[0052] It should be clear that the various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. The present application is not limited to the specific methods described above and shown in the figures. In addition, for the sake of brevity, detailed descriptions of known methods and technologies are omitted here.
[0053] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.
Claims
1. A method for preparing a high temperature resistant diaphragm for a lithium battery, characterized in that: include: Mix water, a dispersant and an inorganic ceramic material uniformly, stir and grind to obtain a mixed solution, wherein the mass ratio of the water, the dispersant and the inorganic ceramic material is (65-75): (0.5-0.8): (35-25); The modified acrylic polymer binder, the polyacrylamide polymer binder, the wetting agent and the mixed solution are uniformly mixed to obtain a high heat-resistant coating slurry, wherein the mass ratio of the modified acrylic polymer binder, the polyacrylamide polymer binder, the wetting agent and the inorganic ceramic material is (1.5-2.5): (1.5-2.5): (0.03-0.06): 100; The high heat-resistant coating slurry is applied to two opposite sides or any one side of a polyolefin base film to form a coating on the corresponding side of the polyolefin base film, and after drying, a high-temperature resistant separator for a lithium battery is obtained.
2. The method for preparing a high temperature resistant separator for a lithium battery according to claim 1, characterized in that: The stirring time of the water, the dispersant and the inorganic ceramic material is 15-60 minutes, and the grinding time is 40-60 minutes.
3. The method for preparing a high temperature resistant separator for a lithium battery according to claim 1, characterized in that: The inorganic ceramic material is any one of alumina, boehmite and silica.
4. The method for preparing a high temperature resistant separator for a lithium battery according to claim 1, characterized in that: The dispersant is polycarboxylate ammonium salt.
5. The method for preparing a high temperature resistant separator for a lithium battery according to claim 1, characterized in that: The modified acrylic acid polymer binder, the polyacrylamide polymer binder, the wetting agent and the mixed solution are stirred for 15-30 minutes.
6. The method for preparing a high temperature resistant separator for a lithium battery according to claim 1, characterized in that: The molecular weight of the polymer in the modified acrylic acid polymer binder is 80,000 to 200,000, and the molecular weight of the polymer in the polyacrylamide polymer binder is 200,000 to 600,000.
7. The method for preparing a high temperature resistant separator for a lithium battery according to claim 1, characterized in that: The wetting agent is a polyether siloxane copolymer.
8. The method for preparing a high temperature resistant separator for a lithium battery according to claim 1, characterized in that: The polyolefin-based film is a polyethylene film or a polypropylene film, and the coating method is roller coating. The thickness of each coating layer is 2-4 μm, the drying temperature is 50-80° C., and the drying time is 30-60 seconds.
9. A high temperature resistant diaphragm for lithium battery, characterized in that: The method is based on the preparation method of the high temperature resistant separator for lithium battery according to any one of claims 1 to 8.
10. Application of the high temperature resistant separator for lithium batteries according to claim 9 in the field of lithium batteries.
Citation Information
Patent Citations
Power lithium ion battery diaphragm and preparation method thereof
CN109524601A
Separator for lithium secondary battery, and lithium secondary battery comprising same
CN113261153A
Separator, method for manufacturing the same, and electrochemical element including the separator
CN118117260A
Separator for electrochemical device and electrochemical device including same
CN119096409A
Cited By
Preparation method of high-temperature-resistant lithium battery cell
CN120767287A
A method for preparing a high-temperature-resistant lithium battery cell
CN120767287B
High-heat-resistance and high-safety composite coating diaphragm for battery and preparation method thereof
CN121584142A